2008
DOI: 10.1089/jmf.2007.003
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide and Soy Isoflavone Suppress Colonic Aberrant Crypt Foci and Cyclooxygenase-2 Expression in Dimethylhydrazine-Treated Rats

Abstract: This study investigated the inhibitory effects of soy isoflavones and fructooligosaccharide (FOS) on colon carcinogenesis. Sprague-Dawley male rats were injected with 1,2-dimethylhydrazine (DMH) and given experimental diets that contained 0%, 3%, 6%, or 9% FOS with or without soy isoflavones (1,000 mg/kg of diet). After 12 weeks, colonic aberrant crypt foci (ACF) formation, cyclooxygenase-2 (COX-2) expression, and fecal bile acid profiles were determined. The numbers of ACF, the numbers of ACF containing four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…16,17 In a previous study we observed an additive effect of high SI dose (1,000 mg=kg of diet) to that of fructooligosaccharide on the formation of aberrant crypt (AC) foci (ACF) and cyclooxygenase-2 (COX-2) expression in rats treated with 1,2-dimethylhydrazine (DMH). 18 The dose, 1,000 mg per kg, was far above normal physiological levels. Similar high doses frequently have been used in many studies of the anticancer efficacy of SIs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…16,17 In a previous study we observed an additive effect of high SI dose (1,000 mg=kg of diet) to that of fructooligosaccharide on the formation of aberrant crypt (AC) foci (ACF) and cyclooxygenase-2 (COX-2) expression in rats treated with 1,2-dimethylhydrazine (DMH). 18 The dose, 1,000 mg per kg, was far above normal physiological levels. Similar high doses frequently have been used in many studies of the anticancer efficacy of SIs.…”
Section: Introductionmentioning
confidence: 94%
“…The numbers of ACF and ACs observed per focus were recorded. 18,22 Measurement of plasma concentrations of genistein, daidzein, and equol Glucuronides and sulfates were hydrolyzed, and genistein, daidzein, and equol were extracted and measured by timeresolved fluoroimmunoassay using genistein, daidzein, and equol kits (Labmaster Ltd., Turku, Finland). 23 All reagents were purchased from Wallac Oy (Turku, Finland).…”
Section: Quantification Of Acfmentioning
confidence: 99%
“…Some studies have indicated that prebiotics such as FOS may play an important role in cancer prevention (Daddaoua et al, 2007;Sung and Choi, 2008). Clark et al (2012) recently reviewed the effect of prebiotics on biomarkers of colorectal cancer (CRC) and concluded that certain prebiotics had the potential to prevent colonic cancer.…”
Section: Prebiotics and Cancermentioning
confidence: 99%
“…A study in obese mice revealed that oligofructose ingestion stimulated secretion of glucagon-like peptide-2 (Cani et al, 2009), a potent intestinal growth factor, in a rat model of DSS-induced colitis (Brubaker et al, 1997). Sung and Choi (2008) found that cyclooxygenase-2 expression in rats treated with dimethylhydrazine, was decreased following FOS administration, and it was proposed that this could represent a potential mechanism of action for certain prebiotics.…”
Section: Prebiotics and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation